A Suggested Training Program Based on the training Needs of Teachers in First Stage of Basic Learning in the light of Developed Mathematics curricula (Journal of Hama University, 2022)
The study aimed to build a proposed training program based on the training needs of teachers, and to achieve the goal of the study, a list of training needs for teachers of the first cycle was prepared. A training program was built in the light of the needs that received great appreciation. The program consisted of 18 training sessions. The training session is divided into two main axes, a theoretical axis based on scientific references in building the theoretical basis for the knowledge specified in the previous goals (cognitive), and a second practical training axis with an applied aspect Of the mathematics curricula developed to develop the required skills, and the research sample amounted to (245) male and female teachers. The study was applied in the first semester of the academic year 2021-2022. The research tools consisted of a training needs questionnaire prepared by the two researchers. The results of the study showed the following:The teachers’ assessment of their needs on the axes of the questionnaire was great for three out of the four axes (lesson planning, lesson implementation, students’ learning assessment), as for the first axis (knowledge and information related to the developed mathematics curricula,) the teachers’ assessment of their needs came to an average.
Keywords: training needs, training program, mathematics teachers, developed curricula